A new companion to Chaucer - Brown, Peter (Blackwell companions to literature and culture, 2019)
Anne of Bohemia and the Parliament of FowlsThe Legend of the Bohemian Amazons; Versions of Anne of Bohemia; Sacral Kingship; Chaucer and Bohemia; Bohemian Piety; Notes; References and Further Reading; Chapter 6 Chivalry; Honor and Shame; The Role of the Church; Love of Women; The Literature of Chivalry; Tournaments; Rejecting Chivalry; Chaucer's Knight and Squire (GP 43-100); The Knight's Tale; Troilus and Criseyde II, 624-31; Ambiguities; "Thy gentillesse cometh fro God allone" (WBT 1162); Notes; References and Further Reading; Chapter 7 Comedy; Medieval Definitions of Comedy